Exploring street vendors’ entrepreneurial potential and gender disparities in an eastern cape port city, South Africa - Hlomendlini, Buchule Mnonopheli; Strydom, Kariena; Asaleye, Abiola John (Asian Development Policy Review, 2023)
This study examines the entrepreneurial potential of informal traders, specifically focusing on street vendors operating in East London, a prominent port city in the Eastern Cape, South Africa. Entrepreneurship, characterised by its dynamic nature entailing visionary foresight and astute exploitation of opportunities, requires agility and fervent dedication in nurturing novel concepts and implementing innovative solutions. Additionally, it aims to address the issue of low female participation in economic activities within this sector. Utilising a structured questionnaire designed for data collection, this research employs both descriptive and inferential statistics to analyze the entrepreneurial traits exhibited by street vendors. The investigation centers on six key independent variables: proactive personality, competitive aggressiveness, risk-taking propensity, perceived capability, perceived opportunity, and innovation. The study’s findings revealed that, among the factors studied, perceived opportunity and innovation were statistically significant contributors to the entrepreneurial potential of street vendors in East London. Moreover, the research identifies that despite demonstrating similar entrepreneurial potential factors as their male counterparts, females exhibit notably lower participation rates within the informal trading sphere. This research holds significant implications for policy formulation and intervention strategies. By highlighting perceived opportunity and innovation as critical factors influencing entrepreneurial potential, the study provides actionable insights for policymakers aiming to enhance the entrepreneurial landscape among street vendors. Furthermore, the identification of gender-specific participation gaps emphasises the need for targeted policies and programs to increase female engagement in informal trading.